2022
DOI: 10.1155/2022/1583773
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Network Pharmacology in Traditional Chinese Medicine

Abstract: Aim. We evaluated the developmental process, research status, and existing challenges of network pharmacology. Moreover, we elucidated the corresponding solutions to improve and develop network pharmacology. Methods. Research data for the current study were retrieved from the Web of Science. The developmental process of network pharmacology was analyzed using HisCite, whereas cooccurrence analysis of countries, institutions, keywords, and references in literature was conducted using CiteSpace. Results. In lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Notably, the rational structural modifications of AChE inhibitors were still the primary route to the discovery of novel One-molecule-multi-target anti-AD drugs at this stage (Rossi et al, 2021;Sang et al, 2022;Turgutalp et al, 2022). Since these two alkaloids' high potential in vitro acetylcholinesterase inhibitory activity had been verified by other researchers (Jia et al, 2021;Tang et al, 2021;Miao et al, 2022). Molecular docking analysis was used to predict the binding mode between these two compounds and AChE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the rational structural modifications of AChE inhibitors were still the primary route to the discovery of novel One-molecule-multi-target anti-AD drugs at this stage (Rossi et al, 2021;Sang et al, 2022;Turgutalp et al, 2022). Since these two alkaloids' high potential in vitro acetylcholinesterase inhibitory activity had been verified by other researchers (Jia et al, 2021;Tang et al, 2021;Miao et al, 2022). Molecular docking analysis was used to predict the binding mode between these two compounds and AChE.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, there are still some problems to overcome. Based on the newly bibliometric analysis results of network pharmacology in TCM, determining the key ingredients in TCM ( Miao et al, 2022 ) just based solely on data from limited databases is not sufficient, which may impact the quality of follow-up research. Researchers believe that this phenomenon occurred because the public databases do not reflect the difference in the composition and content of TCM compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Network construction primarily involves the seamless integration of three crucial types of databases: compound-target related databases, disease-gene related databases, and protein-protein interaction databases. By analyzing the topological properties of drug nodes within the constructed network, the active substances in TCM can be ultimately determined [7,8]. To further enhance the accuracy of predictions, a new network analysis method called Network-based Proximity has been developed to predict drug efficacy [9], and some studies have demonstrated that this method can better identify active molecules in TCM [10].…”
Section: Introductionmentioning
confidence: 99%
“…[4] Network pharmacology can analyze the biological behavior of various drug molecules operating on diverse targets, cells, and organs from the genetic and molecular levels, which can predict and disclose the effects and mechanisms of the different drug molecules. [5] According to the interaction network of "drug-chemical component-target-disease," through network topology analysis, systematically and comprehensively observe and study the intervention and influence of drugs on diseases, revealing the mystery of the multi-molecular properties of drugs that act synergistically on the human body. Network pharmacology has the characteristics of holistic and systemic nature, which coincides with the holistic view of Chinese medicine, and is currently one of the important methods for the discovery of the material basis of Chinese medicine efficacy.…”
Section: Introductionmentioning
confidence: 99%